Anti-Swelling Polyelectrolyte Hydrogel with Submillimeter Lateral Confinement for Osmotic Energy Conversion - Liu, Yongxu; Song, Jiangnan; Liu, Zhen; Chen, Jialin; Wang, Dejuan; Zhi, Hui; Tang, Jiebin; Zhang, Yafang; Li, Ningbo; Zhou, Weijia; An, Meng; Liu, Hong; et al. (Nano-Micro Letters, 2024)
Harvesting the immense and renewable osmotic energy with reverse electrodialysis (RED) technology shows great promise in dealing with the ever-growing energy crisis. One key challenge is to improve the output power density with improved trade-off between membrane permeability and selectivity. Herein, polyelectrolyte hydrogels (channel width, 2.2 nm) with inherent high ion conductivity have been demonstrated to enable excellent selective ion transfer when confined in cylindrical anodized aluminum pore with lateral size even up to the submillimeter scale (radius, 0.1 mm). The membrane permeability of the anti-swelling hydrogel can also be further increased with cellulose nanofibers. With real seawater and river water, the output power density of a three-chamber cell on behalf of repeat unit of RED system can reach up to 8.99 W m−2 (per unit total membrane area), much better than state-of-the-art membranes. This work provides a new strategy for the preparation of polyelectrolyte hydrogel-based ion-selective membranes, owning broad application prospects in the fields of osmotic energy collection, electrodialysis, flow battery and so on. Highlights: 1 Ionic polymers can directly serve as high-performance ion-selective membranes when it was physically confined within submillimeter-sized cylindrical pore. 2 The universality of this strategy is demonstrated in preparing cation/anion-selective membrane. 3 With real seawater and river water, the output power density of a three-chamber cell on behalf of repeat unit of reverse electrodialysis system can reach up to 8.99 W m−2.